Reading Without Words: Cultivating Bi/Multilingual Family Engagement. - Moody, Stephanie M.; Matthews, Sharon D. (Reading Teacher)
Many family literacy programs are designed to teach bi/multilingual families school‐based reading strategies, which often downplays families' rich cultural and linguistic resources and accentuates the gap between home and school literacy. We designed Reading Without Words to investigate how wordless picture books could be used to feature the meaningful literacy practices bi/multilingual families enact. We engaged dozen Spanish–English Latinx bilingual families in the reading of one wordless picture book, and found that interactions with this text cultivated natural family engagement through creative and collaborative oral storytelling, the use of picture‐based evidence, and the flexible application of language. Their reading moves guide our suggestions for traditional family literacy program modifications that highlight the use of wordless picture books and position bi/multilingual families as experts so that educators and families can collaborate to build meaningful literacy practices.